1971
DOI: 10.1128/aem.22.3.393-396.1971
|View full text |Cite
|
Sign up to set email alerts
|

High Aflatoxin Production on a Chemically Defined Medium 1

Abstract: Aspergillus parasiticus ATCC 15517 produced 28 to 30 mg of aflatoxin per 100 ml of a medium containing sucrose, asparagine, and salts in stationary and shaken cultures. In the absence of asparagine in the medium, the toxin yields fell drastically, and the thin-layer chromatograms of the chloroform extracts of the cultures indicated the total absence of aflatoxin G, and the presence of new intense blue and green fluorescent bands having RF values lower than aflatoxins. Initial pH was critical and had to be arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…Other authors have reported accumulation of much higher levels of aflatoxin G 1 than aflatoxin B 1 when large amounts of aflatoxin are produced (Schindler et al, 1967;Reddy et al, 1971). Attempts to identify seventy-seven strains of Aspergillus section flavi belonging to seven species using DNA sequencing determined that A. flavus IFM 40800 and IFM 47030, which are closely related to A. parasiticus, produced aflatoxins B 1 and G 1 (Wang et al, 2001).…”
Section: Dried Figsmentioning
confidence: 99%
“…Other authors have reported accumulation of much higher levels of aflatoxin G 1 than aflatoxin B 1 when large amounts of aflatoxin are produced (Schindler et al, 1967;Reddy et al, 1971). Attempts to identify seventy-seven strains of Aspergillus section flavi belonging to seven species using DNA sequencing determined that A. flavus IFM 40800 and IFM 47030, which are closely related to A. parasiticus, produced aflatoxins B 1 and G 1 (Wang et al, 2001).…”
Section: Dried Figsmentioning
confidence: 99%
“…Most conidial fungi are believed to be relatively unaffected by pH in the range 3-8 in comparison with bacteria (Pitt 1981). Within this range, however, pH is known to affect growth rates and growth limits (Wolf & Wolf 1947;Cochrane 1958;Rosenberg 1975), conidia formation (Hamsa & Ayres 1977;Carels & Shepherd 1978) and germination (Webb 1919;Cochrdne 1958), pigment production (Wolf & Wolf 1947;Hamsa & Ayres 1977;Carels & Shepherd 1978), inhibition by antimycotics (Holmquist et al 1983) and toxin formation (Joffe & Lisker 1969;Reddy et al 1971;Holmquist et al 1983). Studies on the effects of pH in low pH agar media require laborious aseptic titrations of freshly sterilized media (Battley & Bartlett 1966;Holmquist et a/.…”
mentioning
confidence: 99%
“…Thapar (1988) also reported high yields of aflatoxin with organic nitrogen sources especially casamino acids and NH, NO, , while with NH,CI and NaNO, the yields were significantly lower. Payne and Hagler (1983) found that proline stimulated more aflatoxin production than the other nitrogen sources, including the amino acid asparagine, which was previously recognized as supporting good aflatoxin production (Reddy et al 1971). Unlike Davis et al (1966), Payne and Hagler 1983) did not find aspartate to be a good nitrogen source for toxin production.…”
Section: The Role Of Nitrogen Sourcesmentioning
confidence: 92%